Self Regulated Learning (SRL) Ability: Knowledge and Learning Attitudes of Muhammadiyah Students - Sri Hartini; Agus Supriyanto; Said Alhadi; Wahyu Nanda Eka Saputra; Agungbudiprabowo Agungbudiprabowo; Shopyan Jepri Kurniawan (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2018)
The purpose of this study was to identify the level of self-regulated learning (SLR) of students. The research was conducted with a quantitative descriptive method on 300 students at 14 Muhammadiyah Junior High Schools throughout Bantul Regency. The data collection instrument used was a valid and reliable SLR scale, as well as descriptive statistical data analysis with percentages and standard deviation. The results of the study concluded that SRL identification in SMP Muhammadiyah students with high criteria. But even though it has high criteria overall, one school has low criteria because it has access, human resources, and locations that are less relevant to support education. The unequal learning attitudes of students are influenced by human resources as role models, parenting styles, and incoming information. to students about the subject matter. This research can be used by counseling teachers in schools as a basis for developing self-development programs for students.